THE EFFECT OF COMPANY FINANCIAL PERFORMANCE ON STOCK PRICES WITH DIVIDEND PAYOUT RATIO AS INTERVENING VARIABLES IN FOOD AND BEVERAGE SECTOR COMPANIES - Iik Jakataofik; Ekayana S. Paranita; Heri Ispriyahadi (Jurnal Ekonomi, 2023)
This study aims to determine the effect of the company's financial performance on stock prices with dividend payout ratio as an intervening variable in food and beverage sector companies. Dethe science used is researchcausal associative (Causal Relationship) and comparative. The type of data used in this survey is secondary data, with a sample of 14 2015-2021 annual reports of food and beverage companies listed on the IDX.This research uses SPSS and SmartPLS 3 software methods. Result from the research shows that solvency and activity have a significant effect on dividend payout ratio and stock prices, while profitability and liquidity have no significant effect on dividend payout ratios and stock prices. Dividend payout ratio has an effect on stock pricesin food and beverage sector companies on the IDX. Bmeans Dividend payout ratio has an effect on stock prices. Financial performance, which consists of solvency and activity, has an indirect effect on stock prices mediated by the dividend payout ratio, while Profitability and Liquidity have no indirect effect on stock prices mediated by the dividend payout ratio. There is no significant difference between the average stock pricesfood and beverage companies before and during the covid-19 pandemic in Indonesia..